Odpowiedzi

2010-04-12T21:30:23+02:00
A) -3x+5(2x-7)-6(-5x+6) =
-3x+10x-35-(-30x+36) =
7x-35+30x-36 = 37x-71 =
37*(-1)-71 =
-37-71 = -108

b) 5(a-2b)+4(3a+6b)+12 =
5a-10b+12a+24b+12 =
17a+14b+12 =
17*2+14*(-5)+12 =
34-70+12 = -24

c) -(-4xy+3y-2)+7(2xy-x+2y)-(6x+9) =
4xy-3y+2+14xy-7x+14y-6x-9 =
18xy-13x+11y-7 =
18*3*(-2)-13*3+11*(-2)-7
= -90-39-22-7 = -158
3 3 3
2010-04-12T21:34:09+02:00
A)-3x+5(2x-7)-6(-5x+6)=-3*(-1)+5(2*(-1)-7)-6(-5*(-1)+6)=3+5*(-9)-6*11=3-45-66=-108
b)5(a-2b)+4(3a+6b)+12=5*12+4(6-30)+12=60-96=-36
c)-(-4xy+3y-2)+7(2xy-x+2y)-(6x+9)=-(24-6-2)+7(-12-3-4)-(18+9)=-14-133-27=-174
3 2 3